Nærvær - forsøg på en nem definition af leg - Møller, Jørn (Forum for Idræt, 2001)
En fænomenologisk og antropologisk analyse af legen som et universelt, eksistentielt rum for mennesket. Presence – An attempt at an easy definition of play In this article a simple definition of play has been attempted within the framework of phenomenological anthropology. When the process is seen as more serious than the result, we play. When, on the contrary, the result is the more important, we work. To express it in simple formulas in which P is process and R, result: P/R > 1 = Play P/R < 1 = Work The definition is discussed in relation to a number of approsing rations which normally provoke reflexive efforts: play vs. seriousness; play vs. labour; play vs. reality; play vs. war; play vs. sport; play vs. ritual; play as symbol and metaphor. Further, the phenomenological concept of play is contrasted to the pedagogical concept, in an analysis of the instrumental use of play vs. play as a meaningful practise in itself. Finally, reference is made to W.H. Auden’s view of the aesthetic process as a dual act involving sin and the search for redemption.